PENGARUH TEKNIK COPY THE MASTER TERHADAP KETERAMPILAN MENULIS TEKS BIOGRAFI SISWA KELAS X MAN 1 PADANG - Fajri, Meidilla Islamiati; Asri, Yasnur; Afnita, Afnita (Universitas Negeri Padang, 2018)
ABSTRACT This article was written to illustrate the effect of using model Copy The Master techniques on the writing skills of biography text in class X of MAN 1 Padang. This research used quantitative method which usedone group pretest and posttest design. The population of this research in class X MAN 1 Padang. There was 239 population but there was only one class to be the sampel. It was class X IPS 1 which consisted of 32 students that choosen by using purposive sampling technique. Research data is the result of the score in the skill of writing biography text before and after using Copy The Master technique. This study has three result. First, the skill to write biography text in class X MAN 1 Padang before using the Copy The Master technique with an average score of 67,84. Second, the skill of writing biography text of the students of class X MAN 1 Padang aftel using the model imitation technique with an average score of 77,21. Third, based on the t-test at the level of 0.95 obtained tcount >ttabel (3,99 > 1,70). So, it can be said that H1 is accepted. This means that there can be a significant influence on the use of Copy The Master techniques on the writing skills of biography text in class X MAN 1 Padang. Kata kunci: pengaruh, teknik Copy The Master, keterampilan menuli, teks Biografi